Exploring the impact of AI threats on originality and critical thinking in academic writing - Octaberlina, Like Raskova; Muslimin, Afif Ikhwanul; Chamidah, Dewi; Surur, Miftahus; Mustikawan, Alfin (Edelweiss Applied Science and Technology, 2024)
This research aims to provide an in-depth understanding of the impact of AI in academic writing on critical thinking ability, originality of scientific work, intellectual integrity in academia, and AI dependency leading to no improvement in individual thinking ability. Using a qualitative research design focusing on case studies and employing semi-structured interviews, seven undergraduate students in Indonesia were purposively selected to be sampled. The research findings revealed First, AI can threaten the development of individual critical thinking ability, as dependency on this technology reduces active engagement in the process of thinking and reflection, and inhibits creativity. Second, AI has the potential to reduce the originality of academic work, trigger plagiarism, and reduce the analytical quality and creativity of writers. Third, AI can undermine intellectual integrity in academic settings by leading to violations of ethical codes. Fourth, reliance on AI inhibits the improvement of individual thinking skills, as cognitive processes that should be done independently are reduced. Future research could consider more objective measures such as observation or psychometric tests, and investigate more intensive threats in the use of AI in the academic writing environment.